Improving the nutritional status of stunting toddlers through local food nutrition of Javan porridge (Setaria Italica) in Sintang Regency, West Kalimantan - Nur Hayati (BKM Public Health and Community Medicine, 2021)
Objective: Stunting is one of the health problems in Sintang Regency, West Kalimantan Province, with a prevalence of 44.1% in 2017. Sintang Regency targets a reduction in prevalence stunting 3%annually as stated in the Regent's Regulation Sintang Number 20 of 2018 concerning prevention Stunting. In 2018 when the policy began to be implemented, stunting prevalence dropped significantly by 33.2%, but the trend continued to decline in 2019-2020, from 32.7% (2019) to 31.3% in 2020. This shows that the policy has not worked well. One of the innovations that can be done as a sensitive nutrition intervention related to the family's ability to fulfill food is by utilizing local food, namely jatropha seeds, which are processed into porridge as nutrition for toddlers who suffer from stunting. Contents: Jatropha seeds are an authentic food that is easy to find in Sintang Regency at an affordable price. Research conducted by Kurniati (2020) on the effectiveness of giving Javan porridge in increasing weight and height in toddlers stunting in Kayan Hilir District showed significant results after the intervention of giving Javan porridge. The results of the Paired T-Test test obtained a P-value of 0.001. The local government followed up by creating a movement to consume jatropha seeds processed into porridge for toddlers stunting. The health insurance in Indonesia can accept activities that include (1) the formation of small and medium enterprises (SMEs) to manage and package jatropha seeds so that they become marketable products, (2) create educational content on print media and social media that contain the benefits of the nutritional content of jatropha seeds, and (3) socialize the use and processing of local food seeds. Responsibility to the community carried out during posyandu activities. Affordable local food with high nutritional content has the potential to be developed to help improve the nutritional status of toddlers stunting. Tujuan: Stunting merupakan salah satu permasalahan kesehatan di Kabupaten Sintang Provinsi Kalimantan Barat dengan prevalensi mencapai 44,1% pada Tahun 2017. Kabupaten Sintang menargetkan penurunan prevalensi stunting 3% tiap tahunnya yang tertuang pada Peraturan Bupati Sintang Nomor 20 Tahun 2018 tentang Pencegahan Stunting. Pada tahun 2018 saat kebijakan mulai terimplementasi Prevalensi stunting turun secara signifikan sebesar 33,2%, namun pada tahun 2019-2020 trennya semakin menurun yakni 32,7% (2019) menjadi 31,3% pada 2020. Hal ini menunjukkan kebijakan belum berjalan baik. Salah satu inovasi yang bisa dilakukan sebagai intervensi gizi sensitif yang berhubungan dengan kemampuan keluarga untuk memenuhi pangan adalah dengan memanfaatkan pangan lokal yakni biji jawak yang diolah menjadi bubur sebagai nutrisi bagi balita yang menderita stunting. Isi: Biji jawak merupakan makanan asli yang mudah ditemukan di Kabupaten Sintang dengan harga yang terjangkau. Penelitian yang dilakukan oleh Kurniati (2020) tentang efektivitas pemberian bubur jawak dalam peningkatan berat dan tinggi badan pada balita stunting di Kecamatan Kayan Hilir menunjukkan hasil yang signifikan setelah dilakukan intervensi pemberian bubur jawak hasil uji Paired T-Test diperoleh P-value 0,001. Pemerintah Daerah menindaklanjuti dengan membuat gerakan konsumsi biji jawak yang diolah menjadi bubur bagi balita stunting. Kegiatan yang dilakukan antara lain: pembentukan usaha kecil menengah (UKM) untuk mengelola dan mengemas biji jawak agar menjadi produk yang layak dipasarkan, pembuatan konten edukasi pada media cetak maupun media sosial yang memuat manfaat kandungan gizi biji jawak serta sosialisasi pemanfaatan dan pengolahan pangan lokal biji jawak pada masyarakat yang dilaksanakan pada saat kegiatan posyandu. Program inovatif pemanfaatan pangan lokal yang terjangkau dengan kandungan gizi tinggi sangat berpotensi untuk dikembangkan dalam membantu meningkatkan status gizi balita stunting.